Original Article Fine Needle Aspiration Cytology in the Diagnosis of Thyroid Diseases - Syed Qaiser Husain Naqvi, Noor Alain Ansari, Abdul Razaque Qazi, Javaid Mernon (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2012)
Objective: To evaluate the accuracy of Fine Needle Aspiration Cytology ( FNAC ) with comparison of histopathological findings of excised mass in the diagnosis of diseases of thyroid gland. Design: Comparative observational study. Setting & Duration: Departments of Pathology, ENT and Surgical Unit III. Peoples University of Medical & Health Sciences, Nawabshah, during January 2007 to December 2011. Patients & Methods: 126 patients of both sexes were evaluated through detailed history, general physical examination, otolaryngology & neck examination, hormonal assay ( serum T„ T., & ISM &. radio-isotpe scan. All the data were collected on a pre-designed proforma. The FNAC was performed in all cases followed by excision biopsy. The cytological diagnosis was correlated with the histological diagnosis and the results were tabulated. Results: The FNAC results show 112 benign & 14 malignant cases and the histological examination revealed 111 benign & 15 malignant cases, &. proved one case of colloid cyst as nodular goiter, two cases of follicular adenoma as follicular carcinoma, one case of medullary carcinoma as papillary carcinoma, one case of lymphoma as Hashimotos Thyroiditis and one case of uncertain malignancy as papillary carcinoma. The diagnostic accuracy was 89.6%, and the sensitivity, specificity and the positive & negative predictive values detected were 85.7%, 99%, 92.3% & 98.2% respectively. Conclusion: FNAC is a safe, inexpensive and minimally invasive procedure for the diagnosis of thyroid diseases, and is almost free of complications. In our study it is more specific than sensitive with a high diagnostic accuracy.